Penggunaan Aplikasi Instrumen Need Asessment (Studi Kebutuhan) Bimbingan dan Konseling (BK) Berbasis Komputer Sebagai Dasar Perencanaan Program BK Bagi Guru BK di SMP - S, Neviyarni; Adlya, Soeci Izzati; Netrawati, Netrawati; Elfira, Yenni; Dianti, Tiara Maiza (Jurnal Aplikasi IPTEK Indonesia, 2023)
Professional guidance and counseling teachers are expected to master the basic knowledge in the field of guidance and counseling, both theoretical and practical. To support the implementation of duties as a guidance and counseling teacher, it is necessary to have understanding and skills related to needs assessment instrumentation to the preparation of guidance and counseling programs. However, sometimes there are limitations in implementing needs assessment instrumentation, so to make it easier for guidance and counseling teachers in implementing needs assessment instrumentation, a needs assessment instrumentation application was created. This service activity aims to provide understanding, knowledge and skills related to instrumentation applications, needs assessments, and program design based on the results of the needs assessment instrumentation. Skills in identifying needs, interpreting the results of needs assessment instrumentation, compiling guidance and counseling programs and using computer-based guidance and counseling need assessment instrumentation applications. The results show that community service activities regarding the use of computer-based guidance and counseling needs assessment instrumentation applications are in demand and have received positive responses from junior high school guidance and counseling teachers in Agam Regency. Apart from that, it is felt that this activity is very necessary to be given to guidance and counseling teachers who have not received this workshop, then this application is also easy to use in carrying out the duties of guidance and counseling teachers and the material provided is also relevant to the needs of guidance and counseling teachers in schools